KUMYKS’ UPBRINGING TRADITIONS IN THE XIX – EARLY XX CENTURY - Kramynina, Kamilla Magomedrasulovna; Gimbatova, Madina Bagavutdinovna (History, Archeology and Ethnography of the Caucasus, 2019)
The present study aims to consider the specifics of teaching rules of conduct in children in an extended Kumyk family of the XIX – early XX century. Basing on the analysis of a wide range of sources and literature, as well as field ethnographic material obtained in the regions of Kumyks’ concentration, the authors present various aspects of etiquette interaction and pedagogical methods of Kumyk upbringing in the XIX - early XX century. The peculiarities of moral education in Kumyk children, on the example of an extended patriarchal family, have been revealed, since etiquette relations were more pronounced in such families than in a small (nuclear) one. It has been noted that the traditional upbringing among Kumyks was varied and oriented towards the adoption of gender stereotypes by children. The stereotypes of “masculinity” and “femininity”, gender behavior, gender roles and organization of age-sex labor division in a family are analyzed in the paper. On the basis of extensive field material, the authors give examples of various types of games and children activities, which highlight the differences in gender upbringing and the manifestation of “masculinity” and “femininity” in games. It has been established that the existing division of gender roles in a Kumyk family, under which men performed vocational roles, and women – the family ones, formed in children socially accepted ideas of the masculine and feminine types. In the era of globalization, when the institute of traditional family is on the brink of extinction, and gender-neutral upbringing is actively propagated in the mass media, the study of gender stereotypes and features of gender behavior and upbringing in traditional culture has a major scientific and practical importance. The conclusions of the article may be of interest to members of education and culture, or used when writing works in ethnography and pedagogy. The relevance of this study is due to the interest of scholars in various fields and the general public in gender issues and problems of upbringing.